Assistance in Modeling Techniques in Photography and Content Creation of Production Products of KERIAHEN Sewing Skills Course Institution to Expand Marketing through Social Media - Lubis, Suwardi; Sibarani, Robert (Journal of Community Research and Service, 2024)
This program aims to provide assistance to the KERIAHEN Sewing Skills Course Institution in improving knowledge and skills in modeling techniques in photography and visual content creation, as well as expanding marketing through social media. KERIAHEN Institute currently faces challenges in utilizing social media to expand marketing reach and a lack of understanding of modeling techniques in photography. The mentoring method includes identification of needs and challenges, intensive training on modeling and photography techniques, collaboration with photographers and visual creatives, creation of content plans and posting schedules, consultation and mentoring, evaluation, and measurement, as well as dissemination of results and experience sharing. It is expected that through this assistance, KERIAHEN Institute will improve skills in modeling techniques in photography, understand marketing strategies through social media, and be able to produce attractive visual content. This will help the institute in expanding its marketing and increasing its popularity through social media, to attract potential course participants and achieve broader marketing goals.